Risk Analysis of Rice Price in Related to Ceiling Price of Rice Regulation in South Sumatra Province - Lastinawati, Endang; Chuzaimah, Chuzaimah (Musamus Journal of Agribusiness, 2022)
Rice is a basic need of Indonesian people which are sensitive in case of price changes. Various price policies have been implemented by the Government to ensure the stability of rice prices. The aim of this research was to analyse the risk of rice prices before and after the stipulation of rice ceiling price. The research was conducted in South Sumatra Province as one of the national food barns. Price risk was measured using the coefficient of variation analysis and the lower price limit. The data used were the time series data of 78 weeks before and 78 weeks after the stipulation of rice ceiling price. The results show premium rice had a higher price risk than medium rice before stipulation of rice ceiling price. But after the establishment of rice ceiling price, medium rice actually has a higher price risk than premium rice.